2019
DOI: 10.1055/s-0039-1677853
|View full text |Cite
|
Sign up to set email alerts
|

Trauma-Induced Coagulopathy

Abstract: Trauma-induced coagulopathy (TIC) is a heterogeneous entity that contributes to a significant morbidity and mortality following trauma. The activated protein C system, endotheliopathy and platelet dysfunction have been implicated in the pathogenesis of TIC, although there are still controversies on the exact pathogenesis. TIC can be modified by hypoperfusion, acidosis, hypothermia, haemodilution, underlying disease conditions, pre-injury medications as well as genetic predispositions. Current definition of thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
20
0
10

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(30 citation statements)
references
References 78 publications
0
20
0
10
Order By: Relevance
“…EG has the effects of inhibiting platelet adhesion on the endothelial surface, anti-microthrombosis and maintaining coagulationanticoagulant balance. Post-traumatic bleeding, in ammation and other factors lead to abnormal degradation of EG, which may participate in the TIC mechanism 26 . This study revealed SDC1 and HS were both correlated with blood loss and coagulation indexes including Hb, PLT, PT, APTT, AT-III and Ca 2+ .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…EG has the effects of inhibiting platelet adhesion on the endothelial surface, anti-microthrombosis and maintaining coagulationanticoagulant balance. Post-traumatic bleeding, in ammation and other factors lead to abnormal degradation of EG, which may participate in the TIC mechanism 26 . This study revealed SDC1 and HS were both correlated with blood loss and coagulation indexes including Hb, PLT, PT, APTT, AT-III and Ca 2+ .…”
Section: Discussionmentioning
confidence: 99%
“…The receiver operating characteristic (ROC) curves were graphed and area under the curve (AUC) were calculated to investigate the accuracy of indicators for predicting AKI, TIC within 48 hours, and 28-day mortality in trauma group. All statistical tests were two-tailed, and P < 0.05 was considered statistically signi cant.The trauma group had a median ISS of 24(17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29). Main causes of trauma were tra c injuries and falling injuries (53.3% and 31.1%, respectively).…”
mentioning
confidence: 99%
“…1 Acquired haemostatic disorders are being further addressed by Petros in his article on trauma-induced coagulopathy. 2 In recent years, we have learnt relevant details about the pathophysiology and treatment options of both entities.…”
Section: Dear Colleaguesmentioning
confidence: 99%
“…[ 2 ] Progressive trauma-induced coagulopathy is often manifested with increased microparticle and thrombin generation; these have been implicated in the pathogenesis of VTE and organ failure among high-risk populations. [ 3 4 ]…”
Section: Introductionmentioning
confidence: 99%
“…This huge disparity in the reported incidence is influenced by sociodemographic characteristics, nature of the injury, diagnostic modalities used, type and adherence to pharmacologic thromboprophylaxis. [ 3 5 ] Determining the true incidence of VTE and its associated consequences necessitates a thorough understanding of the underlying predisposing factors in trauma patients. Earlier studies have reported various risk factors for VTE in injured patients who require hospitalization.…”
Section: Introductionmentioning
confidence: 99%